Paguristes alcocki Mclaughlin & Rahayu, 2005, n. sp. ... - Mclaughlin, Patsy A.; Rahayu, Dwi Listyo (Zenodo, 2005)
Paguristes alcocki n. sp. (Figs 1–3) ? Paguristes ? ciliatus— Alcock 1905: 34. [Not Paguristes ciliatus (Heller, 1862)]. Paguristes ciliatus.— Gordan, 1956: 321 [in part; literature]. ? Paguristes ciliatus.— Haig & Ball, 1988: 176; Wang, 1992: 59 (list); Wang, 1994: 568; Rahayu, 2000: 392. Not Paguristes ciliatus (Heller, 1862). Paguristes ciliatus.— Wang, 1983: 50 (in part, not pl. 1: fig. 2). Not Paguristes ciliatus Heller, 1892 (see Remarks). Type material. Western Australia: holotype male (7.8 mm), 33 nautical miles N of Rosemary Island, 19°55’S, 116°36’E, 58 m, 29 Nov 1982, WAM C29554. Paratypes, 33 nautical miles N of Rosemary Island, 19°55’S, 116°36’E, 58 m, 29 Nov 1982, 2 males (6.3, 7.5 mm), WAM C16862, C16493; 39 nautical miles north of Enderby Island, 19°58.1’S, 116°27.9’E, 58–59 m, 28 Sep 1982, 1 ovig. female (5.5 mm), WAM C16751. Indonesia: Wamsoi Lagoon, Padaido, Irian Jaya, 57–91 m, 0 4 Feb 1956, 1 male (7.2 mm), RMNH. Philippine Islands: Panglao Expedition, stn L43, off Pamilacan Island, ... : Published as part of Mclaughlin, Patsy A. & Rahayu, Dwi Listyo, 2005, Two new species of Paguristes sensu stricto (Decapoda: Anomura: Paguroidea: Diogenidae) and a review of Paguristes pusillus Henderson, pp. 37-62 in Zootaxa 1083 on pages 40-49, DOI: 10.5281/zenodo.170436 ...